2021
DOI: 10.1177/11786329211024810
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Analysis to Determine the Factors Associated with Institutional Delivery in Nepal: Further Analysis of Nepal Demographic and Health Survey 2016

Abstract: Background: One out of two neonatal deaths and 2 out of 5 maternal deaths occur at home in Nepal. An essential intervention in reducing maternal mortality and neonatal death is institutional delivery. The objective of this study was to find out the external environmental, predisposing, and enabling factors associated with the use of institutional delivery care in Nepal. Methods: Data from Nepal Demographic and Health Surveys (NDHS) 2016 was used to estimate socio-economic, provincial, and use of media differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 33 publications
13
19
0
Order By: Relevance
“…The independent variables included in this study were chosen based on past research and extant literature. 4 , 12 These include the age of the women at birth, place of residence, wealth index, religion, women’s educational level, current marital status, number of antenatal care visits, pregnancy complications, and husband/partner’s educational level.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The independent variables included in this study were chosen based on past research and extant literature. 4 , 12 These include the age of the women at birth, place of residence, wealth index, religion, women’s educational level, current marital status, number of antenatal care visits, pregnancy complications, and husband/partner’s educational level.…”
Section: Methodsmentioning
confidence: 99%
“… 3 According to the United Nations International Children’s Emergency Fund (UNICEF), every day 800 mothers and 2700 babies die as a result of complications during pregnancy and childbirth, according to UNICEF data from 2015. 4 In 2015, the MMR in underdeveloped nations was 239 pregnant women per 100,000 live births, compared to 12 in industrialized countries. The number of women giving birth was high at the end of 2015, and over 303,000 women died during pregnancy, with almost all deaths occurring in low-resource areas and the majority being preventable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exposure variables were divided into ‘institutional facility availability and accessibility’ and ‘population characteristics’ based on Andersen’s healthcare utilization model [ 22 ]. Regarding the institutional facility availability and accessibility, many studies have found that the chance of institutional delivery by trained health personnel is lower for women who live in a rural area because of less convenient or affordable access to a healthcare facility, and norms that may encourage home delivery by a traditional birth attendant (TBA) [ 19 , 25 , 32 , 33 ]. Moreover, other studies have identified the cost of travel and care as barriers to institutional delivery [ 19 , 32 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies from developed and developing countries have applied the Andersen model, such as the United States [ 23 ], Nepal [ 24 , 25 ], Nigeria [ 26 ], and Pakistan [ 27 ] as a framework for conducting research about health service utilization. Thus, it can be expected that the Andersen model is also applicable to a country like ‘Myanmar’ which is not radically different from other developing countries in the region (e.g., Nepal).…”
Section: Introductionmentioning
confidence: 99%